Neke karakteristike notacijskih shema - Tkalac, Slavko; Mateljan, Vladimir (1996)
The paper gives a short review of fundamental knowledge repesentation methods: logical, graphical, structured and procedural notational schemes. Special care is given to notational schemes, classifications and characteristics on which classifications were done.
Projekt MZOS
ENG